2018
DOI: 10.1155/2018/5634826
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Propagation of Electromagnetic Waves with Orbital Angular Momentum at 5.8 GHz

Abstract: Propagation of electromagnetic waves with orbital angular momentum (OAM) is investigated in indoor environments. The OAM modes generated by circular patch array antennas are used. With proper alignment and suppressed multipath, the OAM modes can transport multiple wireless data stream at the same time. Through measurements and ray-tracing simulations, it is found that the advantages of OAM modes are limited if those two conditions are not satisfied. It is also found that multipath effect can be enervated by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This software is based on the ray frustum algorithm [23] for a computational acceleration, which originates from computer graphics and visualization [24], [25]. The ray-frustum-based tracing has also been considered to predict the propagation characteristics of the 5G MMW channel [26], [27] and the orbital angular momentum waves [28] in efficient way.…”
Section: ) Ray-tracing Analysismentioning
confidence: 99%
“…This software is based on the ray frustum algorithm [23] for a computational acceleration, which originates from computer graphics and visualization [24], [25]. The ray-frustum-based tracing has also been considered to predict the propagation characteristics of the 5G MMW channel [26], [27] and the orbital angular momentum waves [28] in efficient way.…”
Section: ) Ray-tracing Analysismentioning
confidence: 99%
“…Only a few of studies have considered OAM transmission in multipath environments. For example, OAM communication has been investigated in an indoor environment [10], where it was found that the OAM communication was sensitive to antenna misalignment and multipath. The multipath effect of specular reflection on OAM communication was studied in [11], where it was shown that higher OAM modes suffer more crosstalk.…”
Section: Introductionmentioning
confidence: 99%